Effectiveness of Group Counseling with a Motivational Interviewing Approach to Improve Students’ Academic Engagement - HL, Muh Nurhidayat; Purwanto, Edy; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2023)
Low academic engagement negatively affects students’ academics, such as poor attendance, lateness, lack of participation in learning, boredom, and some other problems which can cause students dropped out from a school. This study strived for examining the effectiveness of group counseling with a motivational interviewing approach to improve students’ academic engagement and comparing the effects when the intervention as given to students with high career maturity. It used a randomized pretest-posttest comparison group design and involved 30 students grouped into three selected using a random assignment. Their data were taken using academic engagement and career maturity scales with the alpha coefficients of 0.88 and 0.91 respectively. To analyze the data, mixed ANOVA was used. Findings showed that the group counseling with a motivational interviewing approach was effective to improve the academic engagement of students with both high and low career maturity. Further, the improvement was greater in the students with high career maturity. Lastly, implications and limitations are discussed in the discussion section.